Պեդրո Էստալան և «Համաշխարհային ճամփորդը»–ի նրա թարգմանությունը - Սիմոնյան, Հակոբ (Ասողիկ հրատ.)
In 1795-1805 Abbot Pedro Estala published a collection of traveling under the title "The World Traveler or Acquaintance of Old and New Worlds". Pedro Estala was not only a professor of Greek language but also a master of numerous languages. At first his translations were perceived as the simple translation of " Le Voyageur francais о Connaissance de l'ancien et du nouveau monde" by Abbot Joseph de Laporte (1719-1779) (the first 4 volumes), but Iater that point of view was denied, as Pedro Estala, considering it very superficial, continued translating other authors' works (those of the best travelers, as he considered) with his own corrections and changes and as a result published them in 43 volumes. The second volume of the mentioned publication Covers materials about Armenia and its neighboring countries. We present only the translation of the chapter concerning Armenia. Speaking about the Contents of the book it should be noted that it Covers valuable and interesting information about Armenia of the XVth and the XVIth centuries.
Keywords: Մատենագրություն; Թարգմանություն